Exposure-based CFaR in scenario analysis : An application to a rental real estate business - Kuvaja, Alma (My University, 2021)
Cash-Flow-at-Risk (CFaR) specifies the potential expected loss of future cash flow caused by changes in the underlying risk variables for a given confidence level. Exposure-based CFaR is one of the approaches to measure CFaR, which considers both the overall variability of cash flow and the variation caused by individual macroeconomic and market risk variables. This study utilises the exposure-based CFaR approach for cash flow risk assessment of the case company’s rental real estate business. First, by utilizing a multivariate regression model, the exposure of the cash flow to changes in key macroeconomic and market risk variables is investigated. Second, forecasts for the risk variables are generated using an appropriate ARIMA model. Third, the cash flow probability distribution is derived by a Monte Carlo simulation which is based on the risk exposures coefficients, correlation structure between the risk variables and the created forecasts. Finally, the risk bearing capacity of the case company’s cash flow in abnormal market conditions is stress-tested by using hypothetical estimates as predictions of the key risk variables. The results indicate that the cash flow of case company’s rental real estate business is positively exposed to changes in interest rates, real rental income and cost of water supply and sewage. On the contrary, the cash flow is negatively exposed to changes in inflation as well as the cost of heating, maintenance services and repairs. Additionally, the findings show that changes in inflation and interest rates offset each other’s effect on the cash flow, while changes in maintenance and heating costs accentuate the net exposure of the cash flow. The results of the forecast performance measures show that the selected ARIMA models produce more accurate predictions than the naïve method used in studies of Andrén et al. (2005) and Yan et al. (2014) on the exposure-based CFaR method. The findings of the scenario model indicate that, with a 95% confidence level, the cash flow would not fall by more than 24.1% of the expected cash flow over the next eight quarters. Based on the stress tests, the cash flow risk increases if inflation increases while interest rates remain principally unchanged. Altogether, the exposure-based CFaR method can be used to examine the exposure of the rental real estate business to changes in individual risk variables and their combined effect, and to assess cash flow risk based on alternative forecasts of the risk variables.

Cash-Flow-at-Risk (CFaR) arvioi mahdollisen tulevan kassavirran menetysten, joka aiheutuu kassavirran riskitekijöiden muutoksista tietyllä luottamusasteella. Altistumiseen perustuva CFaR on yksi CFaR:n lähestymistavoista, jossa otetaan huomioon sekä kassavirran yleinen vaihtelu että yksittäisten makrotaloudellisten ja markkinariskimuuttujien aiheuttama vaihtelu. Tässä tutkimuksessa käytetään altistumiseen perustuvaa CFaR -menetelmää tapausyrityksen vuokrauskiinteistöliiketoiminnan kassavirtariskin arvioinnissa, mikä perustuu riskimuuttujien altistumiskertoimiin, korrelaatiorakenteeseen ja luotuihin ennusteisiin. Ensinnäkin kassavirran herkkyyttä tärkeimpien makrotalous- ja markkinamuuttujien muutoksille tutkitaan monimuuttujaregressiomallin avulla. Toiseksi riskimuuttujien ennusteet luodaan käyttämällä sopivaa ARIMA-mallia. Kolmanneksi kassavirran todennäköisyysjakauma johdetaan Monte Carlon simulaatiolla. Lopuksi kassavirran riskinsietokyky epänormaaleissa markkinaolosuhteissa testataan stressitesteillä käyttämällä keskeisten riskimuuttujien ennusteina hypoteettisia arvioita niiden kehityksestä. Tulokset osoittavat, että vuokrauskiinteistöliiketoiminnan kassavirta altistuu positiivisesti korkojen, reaalisten vuokratulojen sekä vesi- ja vesihuoltokustannusten muutoksille. Sen sijaan kassavirralla on negatiivinen herkkyys inflaation sekä lämmitys-, huoltopalvelu- ja korjauskustannusten muutokselle. Lisäksi tulokset osoittavat, että inflaation ja korkojen muutokset heikentävät toistensa vaikutusta kassavirrassa, kun taas huoltopalvelu- ja lämmityskustannusten muutokset vahvistavat toistensa vaikutusta. Ennustetarkkuusmittauksen tulokset osoittavat, että valitut ARIMA-mallit tuottavat tarkempia ennusteita kuin naiivi menetelmä, jota aiemmat tutkimukset altistumiseen perustuvasta CFaR -menetelmästä käyttävät. CFaR-pohjaisen skenaariomallin havainnot osoittavat, että 95%:n luottamusasteella kassavirta ei putoa yli 24,1% odotetusta kassavirrasta seuraavan kahden vuoden aikana. Stressitestien perusteella kassavirran riski kasvaa, mikäli inflaatio kasvaa korkotason pysyessä pääosin ennallaan. Tutkimustulosten perusteella voidaan todeta, että altistukseen perustuvalla CFaR -menetelmällä voidaan tutkia vuokrauskiinteistöliiketoiminnan herkkyyttä yksittäisten makrotalous- ja markkinamuuttujien muutokselle ja niiden yhteisvaikutukselle sekä arvioida kassavirtariskiä riskimuuttujien vaihtoehtoisten ennusteiden perusteella.
Keywords: Exposure-based CFaR, Monte Carlo simulation, forecasting, stress testing